ANALISIS PENGARUH PERTUMBUHAN EKONOMI DAN INFLASI TERHADAP PENERIMAAN PAJAK PERTAMBAHAN NILAI DI PROVINSI NUSA TENGGARA BARAT - INDRA DARMAWAN; SAHRI SAHRI; IWAN HARSONO; MUHAMMAD IRWAN (Universitas Mahasaraswati K. Mataram, 2023)
Indonesia's financial performance has been weak, largely due to the state of the macro economy. Value Added Assessment represents ±40% of total revenue and expenses in Indonesia, but over the last 10 years, the implementation of Import Duty Value Added in West Nusa Tenggara has varied and will generally decrease in 2017, 2019 and 2020. This study is intended to describe the effect of financial development and expansion on the implementation of various significant value-added levies in the West Nusa Tenggara Region. This study utilizes optional information from the Measurement Agency and inside information from the Directorate General of Taxes' assessment as the quantity of available business substance, quantity of control areas and cost drives from 2011 to 2022 indicated by the ARDL-ECM strategy. method with association test. The results of this study indicate that economic growth and inflation have an impact on the implementation of value added tax collection in the long term and short term. Economic growth has a positive and significant impact while inflation has a negative and significant impact.